Chip away everything that doesn't look like an elephant - Salt, John D. (Operational Research Society, 2025)
This paper addresses the question of how conceptual models are created in a simulation modelling activity. Assuming an entity-based approach to simulation, some techniques for discovering good entity classes are considered, including personation. Also considered are the notations by which a conceptual model can be represented, and the modes of thought required for good conceptual modelling. Specifically excluded from consideration is the idea of applying a cut-and-dried method. The shortcomings of computers for conceptual modelling are remarked upon.
Keywords: 33 Built Environment and Design; 50 Philosophy and Religious Studies; 3303 Design